Effect of probiotic mixture supplementation to drinking water on the growth performance, carcass parameters and serum biochemical parameters in native turkish geese - Mükremin ÖLMEZ; Tarkan ŞAHİN; Özlem KARADAĞOĞLU; Metin ÖĞÜN; Mehmet Akif YÖRÜK; Sakine DALĞA (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
This study aims to evaluate the eff ects of a probiotic mixture (PM) supplement on the growth performance and the serum biochemical parameters of native Turkish geese. A total of 60 one-day-old goslings were randomly divided into three groups, and each group was divided into four subgroups with five animals each. While no supplement was added to the drinking water of the control group, 0.25 mL and 0.50 mL of PM were supplemented in the drinking water of the PM-1 and PM-2 groups, respectively. The trial was completed in 10 weeks. The results revealed that supplementation of 0.50 mL/L PM in drinking water improved the live weight, live weight gain, feed consumption, feed/gain ratio. The supplementation of PM improved dressing and the liver weight, but it did not have an impact on the heart and gizzard weight of geese. It was also observed that 0.50 mL of PM increased the serum biochemical parameters such as glucose, total protein, albumin, calcium, phosphorus levels. At the same time, it decreased the triglycerides, total cholesterol, LDL-Cholesterol, Aspartate Aminotransferase levels. The present study showed that PM added at 0.50 mL/L in drinking water could be used as a supplement by local breeders for the growth performance of geese.